COMPARED: A solvent vapor explosion in Germany and a combustible dust explosion in the United States. Issue 4 (23rd October 2021) - Cartwright, Paul; Prugh, Richard W.; Ebadat, Vahid
Abstract: Combustible dust explosions and gas/vapor explosions have many features in common—but there are important differences. We take the opportunity to look at two recent industrial explosions and explore the similarities and the differences between solvent vapor and dust cloud explosions as a means of improving our understanding of both dust and vapor explosions.